Novel Nicotine Delivery Systems. (October 2019) - Kumar, P.S.; Clark, P.; Brinkman, M.C.; Saxena, D.
Electronic nicotine delivery systems (ENDS) are devices that contain a power source, a heating element, and a tank or cartridge containing an "e-liquid, " which is a mixture of nicotine and flavoring in a glycerol–propylene glycol vehicle. Their increasing popularity among adolescents might be attributed to aggressive marketing in physical venues, social media outlets, as well as irreversible changes caused by nicotine in the developing brains of youth and young adults, predisposing them to addictive behaviors. Adolescent ENDS users were 4 times more likely to initiate cigarette smoking, and the odds of quitting smoking were lower and, in many instances, delayed for those using ENDS. ENDS also renormalize cigarette-like behaviors, such as inhaling/exhaling smoke. The oral cavity is the initial point of contact of ENDS and the first affected system in humans. Oral health depends on an intricate balance in the interactions between oral bacteria and the human immune system, and dysbiosis of oral microbial communities underlies the etiology of periodontitis, caries, and oral cancer. Emerging evidence from subjects with periodontitis as well as periodontally healthy subjects demonstrates that e-cigarette use is associated with a compositional and functional shift in the oral microbiome, with an increase in opportunistic pathogens and virulence traits.